1982
DOI: 10.1111/j.1467-2494.1982.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of avocado and soya bean lipidic non‐saponifiables on the components of skin connective tissue after topical application in the hairless rat: biophysical and biomechanical determination

Abstract: Synopsis The non-saponifiable lipidic fractions of avocado and soya bean applied percutaneously to hairless rats for 15 days had been shown to produce biochemical modifications of dermal connective tissue components: increases of soluble collagen and of the ratio soluble collagen/insoluble collagen. In this present study, we tried to show whether these biochemical modifications could be confirmed by biophysical analytical methods and could affect the biochemical properties of the skin. The experiments were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In addition to an increase in the solubility of collagen, behavior that is attributed to a decrease in the activity of lysyl oxidase was observed [66]. A similar conclusion was proposed by Lamaud et al [71], stating that the mixture of soybean and avocado oils decreased the degree of collagen cross-linking, a process that has been associated with a delay in wound healing. However, Oliveira et al [53] indicated that the healing activity of a semi-solid formulation of avocado oil (50/50 Vaseline) and avocado pulp oil promoted the increase of collagen synthesis and decreased the number of inflammatory cells during the process of wound healing.…”
Section: Biological Effectsmentioning
confidence: 56%
“…In addition to an increase in the solubility of collagen, behavior that is attributed to a decrease in the activity of lysyl oxidase was observed [66]. A similar conclusion was proposed by Lamaud et al [71], stating that the mixture of soybean and avocado oils decreased the degree of collagen cross-linking, a process that has been associated with a delay in wound healing. However, Oliveira et al [53] indicated that the healing activity of a semi-solid formulation of avocado oil (50/50 Vaseline) and avocado pulp oil promoted the increase of collagen synthesis and decreased the number of inflammatory cells during the process of wound healing.…”
Section: Biological Effectsmentioning
confidence: 56%
“…Research has been conducted on the effect of topical administration of avocado fruit extract on wound models in rats, revealing faster re-epitheliazation and higher hydroxyproline content of the repaired wound [ 95 ]. The topical application of avocado oil in rats has also been shown to increase collagen synthesis and decrease the numbers of inflammatory cells during the WH process [ 94 , 96 ].…”
Section: The Potential Beneficial Effects Of Topical Application Omentioning
confidence: 99%
“…The oil was dermally applied once a day for 14 days. The results showed that avocado oil, used alone or in a dermal formulation (50% avocado oil in petrolatum), increased collagen synthesis and reduced the number of inflammatory cells throughout the wound‐healing process (de Oliveira et al, ; Lamaud et al, ).…”
Section: Monounsaturated Fatty Acid‐based Butters/oilsmentioning
confidence: 99%
“…Vegetable butters and oils have shown promising results in in vitro and in vivo studies. They affect phases of the wound‐healing process through their bacteriostatic, antimicrobial, anti‐inflammatory, and antioxidative activities and by promoting cell proliferation, increasing collagen synthesis, stimulating dermal reconstruction, and repairing the skin's lipid barrier function (Cornily et al, ; de Oliveira et al, ; Lamaud, Huc, & Wepierre, ; Lewinska, Zebrowski, Duda, Gorka, & Wnuk, ; T.‐K. Lin, Zhong, & Santiago, ; Mandawgade & Patravale, ; Nasopoulou, Karantonis, Detopoulou, Demopoulos, & Zabetakis, ; Shinagawa, de Santana, Torres, & Mancini‐Filho, ; Vaughn, Clark, Sivamani, & Shi, ).…”
Section: Introductionmentioning
confidence: 99%